Deciding their destinies: the impact of remittances and other socio-economic determinants of course selection decision of the eldest sibling in Pasay and Eastern Samar, Philippines - de Guzman, Errica Marie N. (Animo Repository, 2009)
This paper examines the impact of remittances and other determinants to the course selection of the eldest child in the Philippines. Five course groups were taken into consideration for this study. The selection was based on the courses that had the highest number of graduates taken from the government records. The five course groups chosen were Education, Commerce, Engineering, Health and Pure Sciences and Information Technology. Several determinants were accounted for and finally segregated due to availability of data. The study then employed five binominal logit regressions while deriving the marginal effects of each to capture the probabilities of taking up the courses. Estimation results were mixed and even counter-intuitive for some courses. Sex was the only variable that was consistent among all the variables under analysis. While for remittances, it negatively affected the probability of taking up Education while it does otherwise for Health and Sciences.